The linear equation is [tex]y = -\frac{5}{3}x + \frac{26}{3}[/tex]
The points are given as: (7,-3) and (4,-8)
The equation is then calculated using:
[tex]y = \frac{y_2 -y_1}{x_2 -x_1} *(x - x_1) + y_1[/tex]
Substitute the known values
[tex]y = \frac{-8+3}{4-7} *(x-7) - 3[/tex]
Evaluate
[tex]y = -\frac{5}{3} *(x-7) - 3[/tex]
Expand
[tex]y = -\frac{5}{3}x + \frac{35}{3} - 3[/tex]
Evaluate the sum
[tex]y = -\frac{5}{3}x + \frac{26}{3}[/tex]
Hence, the equation is [tex]y = -\frac{5}{3}x + \frac{26}{3}[/tex]
Read more about linear equations at:
https://brainly.com/question/14323743
#SPJ1